2019
DOI: 10.2147/idr.s223085
|View full text |Cite
|
Sign up to set email alerts
|

<p>Antagonistic Effects Of Baicalin On <em>Mycoplasma gallisepticum</em>-Induced Inflammation And Apoptosis By Restoring Energy Metabolism In The Chicken Lungs</p>

Abstract: BackgroundBaicalin possesses potential anti-inflammatory, anti-tumor and anti-oxidant activities. In the present study, we attempted to investigate the preventive effects of baicalin against Mycoplasma gallisepticum (MG)-induced inflammation, apoptosis and energy metabolism dysfunction in chicken lungs.MethodsExperimental chickens were randomly divided into 1) control group, 2) MG infection group, 3) MG-infected group treated with baicalin at a dose of 450 mg/kg and 4) baicalin alone treated group (450 mg/kg).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…These results are consistent with the results of apoptosis which proved that MG infection causing the depletion of CD8 + cells might be due to apoptosis. Our previous studies also revealed that MG induced apoptosis in chicken lungs and spleen 36,59 . Hence, we speculate that the depletion of CD8 + cells in chicken BF could be the possible cause of immune impairment during MG infection.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…These results are consistent with the results of apoptosis which proved that MG infection causing the depletion of CD8 + cells might be due to apoptosis. Our previous studies also revealed that MG induced apoptosis in chicken lungs and spleen 36,59 . Hence, we speculate that the depletion of CD8 + cells in chicken BF could be the possible cause of immune impairment during MG infection.…”
Section: Discussionmentioning
confidence: 56%
“…Baicalin treatment was started after 3 days of challenge. Baicalin powder was first dissolved in distilled water and given orally once a day as mentioned previously 36 . Chickens were sacrificed after 7 days of baicalin post‐treatment and BF samples were collected for experimental analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports showed that factors such as high feeding density, heat and/cold stresses, excessive ammonia, accumulation of feces, fouling of the chicken house, excessive temperature differences, and sudden changes in climate can contribute to the spread and outbreak of disease ( Hochachka and Dhondt, 2000 ; Ley, 2003 ). Mycoplasma gallisepticum infection caused major economic losses in terms of reduced weight gain, egg production and hatchability, downgrading carcass quality, and the infected birds become susceptible to other diseases ( Beaudet et al., 2017 ; Ishfaq et al., 2019a ). Mycoplasma gallisepticum is a continuing problem in poultry and efforts to prevent the losses in commercial flocks particularly in layer and breeders including bacterin-based vaccines, killed vaccines, and live vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Baicalin suppressed inflammation mainly through suppression of toll-like receptors and nuclear factor kappa-B (NF-ÎșB) pathway ( Ming et al., 2018 ). Earlier studies explained that baicalin interacted with various signaling pathways and ameliorated MG-induced inflammation in chicken thymus ( Li et al., 2019 ), spleen ( Ishfaq et al., 2019a ), DF-1 cells ( Wu et al., 2019a ) and lungs ( Ishfaq et al., 2019b ). In addition, baicalin proved effective against E. coli or LPS-induced inflammation in various experimental animals ( Nagaki et al., 2001 ; Cheng et al., 2017 ; Zhao et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%